Synthesis of biphenyl bridged dendritic mesoporous organosilica with extremely high adsorption of pyrene. Issue 19 (29th April 2019) - Theivendran, Shevanuja; Zhang, Jun; Tang, Cheng; Kalantari, Mohammad; Gu, Zhengying; Yang, Yannan; Yang, Yang; Strounina, Ekaterina; Du, Aijun; Yu, Chengzhong
Abstract : This paper presents the synthesis of biphenyl bridged dendritic mesoporous organosilica nanoparticles (BDMONs) and the important role of biphenyl groups in the adsorption of pyrene. Abstract : The development of functional materials with high adsorption performance towards polycyclic aromatic hydrocarbons (PAHs) such as pyrene is important for environmental protection and human health. Herein, for the first time, we report the synthesis of biphenyl bridged dendritic mesoporous organosilica nanoparticles (BDMONs) by using a co-solvent-assisted approach. It is demonstrated that biphenyl bridged groups in nano-adsorbents play an important role in their adsorption performance for PAH with multiple fused aromatic rings. Compared to their counterpart with a phenyl bridged group, BDMONs exhibit lower adsorption energy towards pyrene and three times higher adsorption capacity (∼2.5 g g −1 ), with nearly all the porous space being utilized for adsorption.